Navigating the "Grammar of Resistance": A Micro-Political Analysis of How New Contractual Head Teachers Overcome Institutional Inertia in Rural Pakistani Schools - Javed Ali Rajpar; Abul Ala Mukhtar; Shahid Hussain Wassan (Journal of Religion and Society, 2025)
The educational system of Sindh is marked by a long-standing and deep-seated system crisis that has remained untouched by the conventional top-down reform initiatives over the decades. Having about 23 million out-of-school children in Pakistan, and almost 7.4 million of that number living in Sindh alone, the province is struggling with some of the worst educational pointers in the South Asian region. In addition to the sheer number of out-of-school children, the quality of teaching in government schools is also utterly dismal, with standardized testing like the ASER and the SAT having repeatedly revealed that a large majority of students are not even able to master basic grade level skills in literacy and numeracy skills. This has been seen to fail in the past due to a recruitment system that is entrenched in the concept of political patronage whereby head teachers and faculty are not necessarily hired because they are more meritocratic or demonstrating leadership skills but due to their long tenure or political affiliation. This paper discusses one such ambitious policy reform by the Government of Sindh, namely the merit-based hiring of contractual head teachers or IBA head teachers, charged with the responsibility of becoming change agents in some of the most under-resourced and bureaucratically stuck schools in the province. This paper is based on a qualitative multiple-case study of three such head teachers in rural District Khairpur, and it states that the school change process in these settings is micro-political in nature. Although policy texts tend to present leadership in a technical-rational manner, the actual life of these new head teachers is one of perpetual negotiation, conflict and maneuvers. The main argument is that these leaders were successful not because of their formal positional authority, which was frequently compromised by their contractual position, but because of their capacity to mobilize an extensive arsenal of symbolic, relational and procedural tactics to defeat deep-seated “institutional inertia”. The paper will compare three different schools (Sojhro Khan, Thar Deep, and Shahpur) and will show that the nature and the intensity of resistance are highly situational, as the passive resistance experienced by HT1 was relatively low-stakes, whereas the opposition faced by HT3 was high and even life-threatening. Using this micro-political prism, the research hypothesizes that political cunning and local legitimacy-creating capacity is as important as managerial skill among leaders working in the weak institutional contexts in developing states. Keywords: Navagating, Resistence, Micro-Political, Contractual, Organization, Feudalistic.